Ownership in East-Asian Aid Discourses. Issue 3 (2nd September 2017) - Burghart, Sabine
Abstract: Ownership is commonly regarded a central precondition for aid effectiveness. Some scholars argue that ownership reflects Japan's aid philosophy but that its interpretation is distinct from the understanding in the (Western) aid community [e.g. Lehman, Howard P. (2010) Japan and Africa: Globalization and foreign aid in the twenty-first century, London: Routledge; Ohno, Izumi and Kenichi Ohno (2008) 'Ownership of what?: Beyond national poverty strategies and aid harmonisation in the case of Vietnam', in Alf Morten Jerve, Yasutami Shimomura and Annette Skovsted Hansen, eds, Aid relationships in Asia: Exploring Ownership in Japanese and Nordic Aid, Basingstoke: Palgrave Macmillan, pp. 41–62.]. China and South Korea – formerly Japan's main aid recipients in East Asia – experienced rapid economic development with little donor intervention. This experience has shaped the countries' approaches towards official development assistance (ODA) in general, and their understanding of ownership in particular. While the three East-Asian donors are usually compared in terms of aid volume, regional and sectoral allocation, forms of aid, etc. (e.g. Huang, Meibo (2016) 'Policies and practices of China's foreign aid: A comparison with Japan', in Hiroshi Kato, John Page and Yasutami Shimomura, eds, Japan's Development Assistance: Foreign Aid and the Post-2015 Agenda, Basingstoke: Palgrave Macmillan, pp. 135–148; Stallings, Barbara and Eun Mee Kim (2016) 'Japan, Korea and China: Styles of ODA in East Asia', in Hiroshi Kato, John Page and Yasutami Shimomura, eds, Japan's Development Assistance: Foreign Aid and the Post-2015 Agenda, Basingstoke: Palgrave Macmillan, pp. 120–134], their interpretation of ownership has received less attention. This is where this comparative study aims to contribute. For this purpose, 37 official ODA documents were analysed. The findings confirm a set of similarities but also reveal some differences of the East-Asian donors' approach to ownership. They indicate a basic understanding of aid as mutually beneficial cooperation rather than a charitable action to the poor. However, East-Asian donors view themselves in different roles in the aid relationship: Japan emphasises its role as a global leader, China presents itself as a primus inter pares and South Korea's position unifies several roles. The documents further stress the aspects of 'self-help' and 'self-reliance'. Compared to Japan and South Korea, Chinese sources are most outspoken on the principle of non-interference in recipient countries but at the same time indicate a certain economic conditionality.